EFFECT OF EPOXIDIZED NATURAL RUBBER AS A COMPATIBILIZER IN SILICA-FILLED STYRENE BUTADIENE RUBBER COMPOUND - Indra Surya, Siswarni MZ (Jurnal Teknik Kimia USU, 2014)
By using a semi-efficient vulcanization system, the effect of Epoxidized Natural Rubber (ENR) as a compatibilizer in silica-filled Styrene Butadiene Rubber (SBR) compound was carried out. The ENR was incorporated into the silica-filled SBR compound at 5.0 and 10.0 phr. An investigation was carried out to examine the effect of ENR on cure characteristics and tensile properties of the silica-filled SBR compound. It was found that ENR gave enhanced cure rate to the silica-filled SBR compound. ENR also exhibited a higher torque difference, tensile modulus, and tensile strength up to 10.0 phr. The study of rubber - filler interaction proved that the addition of ENR to the silica-filled SBR system improved the rubber - filler interaction.